Importance of Ganja Sebzikar Monument in the Study of Tolerance Culture Traditions - Hasanov, Elnur (Scholarya Demo Journal of Ruby, 2020)
This paper investigates Sebzikar grave-yard as an important medieval monument of Ganja city from the historical and ethnographic point of view. Located in the ancient quarter Sebzevad, this cemetery is a historical and architectural complex of local importance. Grave-yard has preserved many material and cultural samples, historical sources tombstones, epitaphs, ancient tombstones epigraphic sources. This significant monument has a rich history of more than five centuries. There are more than one hundred tombs and graves in Sabzikar grave-yard. Among these monuments, tombs and graves of the descendants of the city’s outstanding clans have the main importance. For the first time in this research, significance of Sebzikar monument was studied in investigation of multicultural values in Ganja city, which has an ancient and rich historical past, as well as in the formation and preservation of the traditions of a culture of peaceful coexistence tolerance. Along with the ancient tombs preserved in this unique historical and architectural complex to this day, the characteristic features of the gradually destroyed tombs were studied on the basis of various written sources, scientific works, archival documents and historical sources. The importance of the Sebzikar monument as an important example of pan-Islamic spiritual and material culture, an open-air museum, its significance as a material source in the study of tolerance traditions in Ganja, as well as in the development of architectural and local craft traditions, which are the important indicators of urban culture, were also investigated in scientific article based on academic sources.